Hyper-Progressive Disease (HPD) during Immune Checkpoint Inhibitor (ICI) Therapy - Jain, Arpit; Koyyala, Venkata Pradeep Babu; Narayan, Satya; Soni, Satyajeet; Redhu, Pallavi; Jaju, Akanksha (Indian Journal of Medical and Paediatric Oncology, 2022)
Immune checkpoint inhibitor (ICI) restores an efficient antitumor T cell response against tumor cells fostering durable responses that can persist even after the treatment. However, these treatment effects can manifest as an unusual pattern of disease progression, pseudo-progression, or hyper-progression. Differentiating hyper progressive disease (HPD) from pseudo-progression has significant clinical implications and further decision-making for the patient on ICI. HPD is a dramatic acceleration of the rate of tumor progression with the advent of immunotherapeutic agents causing detrimental effects on the disease outcome.
Keywords: hyper-progression; immunotherapy; medical oncology; PD1/PDL1